Microstructure-based simulation of thermomechanical behavior of composite materials by object-oriented finite element analysis - Chawla, N.; Patel, B.V.; Koopman, M.; Chawla, K.K.; Saha, R.; Patterson, B.R.; Fuller, E.R.; Langer, S.A. (Materials characterization, 2002)
While it is well recognized that microstructure controls the physical and mechanical properties of a material, the complexity of the microstructure often makes it difficult to simulate by analytical or numerical techniques. In this paper we present a relatively new approach to incorporate microstructures into finite element modeling using an object-oriented finite element technique. This technique combines microstructural data in the form of experimental or simulated microstructures, with fundamental material data (such as elastic modulus or coefficient of thermal expansion of the constituent phases) as a basis for understanding material behavior. The object-oriented technique is a radical departure from conventional finite element analysis, where a “unit-cell” model is used as the basis for predicting material behavior. Instead, the starting point of object-oriented finite element analysis is the actual microstructure of the material being investigated. In this paper, an introduction to the object-oriented finite element approach to microstructure-based modeling is provided with two examples: SiC particle-reinforced Al matrix composites and double-cemented WC particle-reinforced Co matrix composites. It will be shown that object-oriented finite element analysis is a unique tool that can be used to predict elastic and thermal constants of the composites, as well as salient effects of the microstructure on local stress state.